2001
DOI: 10.1021/jm010853h
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design, Synthesis, and Biological Evaluation of Conformationally Restricted Novel 2-Alkylthio-6-[1-(2,6-difluorophenyl)alkyl]- 3,4-dihydro-5-alkylpyrimidin-4(3H)-ones as Non-nucleoside Inhibitors of HIV-1 Reverse Transcriptase

Abstract: 5-Alkyl-2-(alkylthio)-6-(2,6-difluorobenzyl)-3,4-dihydropyrimidin-4(3H)-ones (S-DABOs, 2) have been recently described as a new class of human immunodeficiency virus type 1 (HIV-1) non-nucleoside reverse transcriptase (RT) inhibitors (NNRTIs) active at nanomolar concentrations (Mai, A. et al. J. Med. Chem. 1999, 42, 619-627). In pursuing our lead optimization efforts, we designed novel conformationally restricted S-DABOs, 3, featuring a methyl at the benzylic carbon (Y = Me) and at the pyrimidine 5-position (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 48 publications
7
120
1
Order By: Relevance
“…10 One compound related to the above derivatives and having two stereogenic centers was resolved into four stereoisomers by HPLC on Chiralpak IA chiral stationary phase (CSP) using ethyl acetate-based eluents. 11 The assignment of absolute configuration by X-ray diffraction analysis was not possible because of unfavorable physical properties of isolated stereoisomers and difficulty to obtain crystalline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…10 One compound related to the above derivatives and having two stereogenic centers was resolved into four stereoisomers by HPLC on Chiralpak IA chiral stationary phase (CSP) using ethyl acetate-based eluents. 11 The assignment of absolute configuration by X-ray diffraction analysis was not possible because of unfavorable physical properties of isolated stereoisomers and difficulty to obtain crystalline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds MC1838 and MC1839, which share a chiral center at the benzylic position, were prepared and tested as racemates. In previous DABO studies, [9][10][11]15] the R enantiomer of related derivatives was predicted as the most active; studies are in progress to confirm this hypothesis for this series as well.…”
Section: Resultsmentioning
confidence: 70%
“…[2] Since then, a great number of oxopyrimidines have been synthesized and tested as anti-HIV-1 agents to obtain more potent and selective compounds. Structure-activity relationship (SAR) profiles of DABOs together with molecular modeling investigations of their putative binding modes have shown that the presence of a C2-alkoxy (DABOs), [3][4][5] -alkylthio (S-DABOs), [6][7][8][9] or -alkylamino (NH-DABOs) [10,11] side chain is a structural determinant for the antiviral activity of these derivatives. Moreover, 2,6-difluoro substitution on the C6-phenylmethyl moiety and the introduction of a methyl group at the pyrimidine C5-position and on the methylene bridge that connects the pyrimidine and phenyl rings (benzylic position) furnished new conformationally restricted compounds with nanomolar activity against wild-type HIV-1 and sub-micromolar activity against the Y181C mutant strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudbeck et al have performed derivatization of DABO by modelling studies of potent 1-[(2-hydroxy ethoxy) methyl]-6-(phenylthio) thymine (HEPT) and by the substitution of benzyl moiety with phenyl thio moiety at the C-6 position of the pyrimidine ring [29]. A structure-activity relationship (SAR) profile of DABOs together with molecular modeling investigation on their putative binding mode have shown that the presence of a C-2-alkoxy (DABOs), C-2-alkylthio (S-DABOs), or C-2-alkylamino (NH-DABOs) side chain is the structural determinant for the antiviral activity of these derivatives, with the length and size of the C-2 side chain having only modulator effects on potency [30][31][32][33][34]. The 2,6-difluoro substitution at the C-6-benzyl moiety of S-DABOs and NH-DABOs produced favorable π-stacking interactions with the Tyr188 side chain into the non-nucleoside binding site (NNBS), leading to compounds (F2-S-DABOs and F2-NH-DABOs) active in the nanomolar range.…”
Section: Introductionmentioning
confidence: 99%